APPLICATION OF THE FOREST SHIELDING FACTOR TO THE MAXIMUM-LIKELIHOOD EXPECTATION MAXIMIZATION METHOD FOR AIRBORNE RADIATION MONITORING. Issue 3 (5th June 2019) - Sasaki, M; Sanada, Y; Yamamoto, A
Abstract: The maximum-likelihood expectation maximization (ML-EM) method is expected to improve the accuracy of airborne radiation monitoring using an unmanned aerial vehicle. The accuracy of the ML-EM method depends on various parameters, including detector efficiency, attenuation factor, and shielding factor. In this study, we evaluate the shielding factor of trees based on several field radiation measurements. From the actual measurement, the shielding factors were well correlated with the heights of the trees. The evaluated shielding factors were applied to the ML-EM method in conjunction with the measured data obtained from above the Fukushima forest. Compared with the conventional methods used for calculating the dose rate, the proposed method is found to be more reliable.